Prospective analysis about informal labor, ambulant sales and social security in San José, C.R for the period 2020-2025 - Herrera Rodríguez , Daniela (2022)
The statistics of informal labor in the world are rising and Costa Rica is not exempt. In the country, the amount of formal and informal workers are equal; so, it is a subject that requires immediate attention. This investigation was focused on the ambulant vendors of the downtown of San José (Costa Rica). It is a fact that the informal workers are unprotected in terms of social security, for that reason, a prospective methodology was used to determinate the real access possibilities for a group of 30 ambulant vendors to the social security of the CCSS; taking into account the cost-benefit analysis of the definition of formality nowadays. In addition, the socioeconomic data of the ambulant vendors of San José were generated and used to create a prospective analysis that combined quantitative and qualitative variables, to determine if the social security of the ambulant vendors would improve in the next five years.